Intellectual character of metacognition in thinking strategies - Ayu Niza Machfauzia; Dr Djohan; Phakkharawat Sittiprapaporn (Asian Journal of Medical Sciences, 2020)
Background: Metacognition is one aspect of intellectual character about a concept that has been used to refer to a variety of epistemological processes. Metacognition essentially means cognition about cognition; that is, it refers to second-order cognitions: thoughts about thoughts, knowledge about knowledge or reflections about actions. Previous research explained that metacognition is useful in many educational settings and can be transferred from the music classroom to other subject areas.